Distal hypospadias repair using the needle point bipolar cutting–coagulation forceps. Issue 1 (February 2020) - Bagnara, V.; Giammusso, B.; Castagnetti, M.; Esposito, C.; Bianchi, A.
Summary: Introduction: To determine the outcome of distal hypospadias repairs performed using bipolar diathermy (BD) for all the dissection. Methods: Retrospective review of 310 patients undergoing distal hypospadias (264 subcoronal/distal penile and 46 coronal/glanular) over a 11-year period. Median age at surgery was 2.0 years (range 9 months–15 years). Caudal anesthesia was performed in all patients. All children underwent an in situ tubularization of the urethral plate, which was combined with midline incision of the plate in 30 (10%). Preputial reconstruction was performed in 303 (98%) patients. BD forceps was used for coagulation and for all the dissection including skin incision, elevation of glans wings, separation of the corpus spongiosum from the corpora cavernosa, and urethral plate incision, when deemed appropriate. The authors assessed surgical complications and cosmetic results. The latter using the hypospadias objective score (HOSE), with a score ≥ 14 considered as acceptable. Results: The average operative time was 70 min. There was no postoperative bleeding or hematomas that required surgical intervention. There were no wound infections or necrosis. Complications occurred in 37 patients (11.9%). Urethral fistula formation was the commonest ( n  = 18). Postoperative persistent preputial swelling occurred in 3.5% of cases. Two hundred twelve patients (90.6%) had a HOSE score ≥ 14, and no patient required revision surgery for skin problems after a median follow-up of 8.1 (range 1.2–13.1) years. Discussion: The study is limited by its retrospective nature and by the fact that a number of other pre-operative, intra-operative, and postoperative variables can affect outcome. Conclusions: Bipolar diathermy can be safely used for distal hypospadias repairs. It allowed careful control of intra-operative bleeding and also clear visualization of tissue planes. Complication rate overall compares favorably with the literature, and cosmetic results were satisfactory. Table Results of hypospadias repairs using the bipolar diathermy technique Table   All patients ( n  = 310) % Fully healed 273 88.1 Urethral fistula 18 6 Partial or total urethroplasty dehiscence 6 2 Complete dehiscence 7 2.2 Preputial fistula 2 0.6 Severe urethral meatal stenosis 2 0.6 Persistent chordee 2 0.6